2014
DOI: 10.3109/03009734.2014.941049
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine pretreatment alleviates propofol injection pain

Abstract: ObjectiveThe incidence of propofol injection pain during induction of general anesthesia varies from 28% to 90%. This prospective, randomized, double-blind, placebo-controlled study evaluated the effect of dexmedetomidine (DEX) for reducing the incidence and severity of propofol injection pain.MethodsPatients undergoing elective surgical procedures were randomly allocated into seven groups of 30 patients each. Experimental treatments were intravenously administered over 10 min (total volume 10 mL) prior to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…[ 5 6 ] Dexmedetomidine a newer α adrenergic agonist has been used to alleviate propofol injection pain. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 6 ] Dexmedetomidine a newer α adrenergic agonist has been used to alleviate propofol injection pain. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Many studies which aimed to reduce propofol injection pain have been performed [9], and the preventive effects of dexmedetomidine were reported in some studies [10,11]. Li et al [12] performed a randomized controlled study to examine the attenuation effect of dexmedetomidine pretreatment for propofol injection pain in 137 patients who underwent electroconvulsive therapy.…”
Section: Intraoperative Dexmedetomidine For Intra and Postoperative Pmentioning
confidence: 99%
“…Nevertheless, its adverse cardiovascular and hemodynamic effects and swelling at its injection site need to be further studied (14,15). Recent reports have shown that dexmedetomidine (Dex-) is as highly effective in attenuating propofol-induced pain as lidocaine (6,16). On the other hand, Dex-is a highly selective alpha-2 adrenoceptor agonist and exhibits analgesic, sedative, and sympatholytic properties that regulate the incidence and intensity of propofol injection pain.…”
Section: Introductionmentioning
confidence: 99%